1989
DOI: 10.1007/bf00344187
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillosis of the sphenoid sinus simulating a pituitary tumor

Abstract: Sphenoidal aspergillosis is an unusual cause of sella turcica enlargement. Pituitary abscess secondary to Aspergillus had been reported. In the present case, a woman with sphenoid sinus aspergillosis mimicked a pituitary tumor. This patient survived her infection with intact pituitary function following a transsphenoidal approach. No postoperative amphotericine-B and 5-fluorocytosine were necessary. CT scan revealed a mass occupying the sphenoid sinus extending to the sella turcica. Factors that should alert t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 8 publications
0
11
0
2
Order By: Relevance
“…Pituitary aspergillosis is an extremely rare presentation for Aspergillus infection and is often misdiagnosed as a pituitary tumor . To our knowledge, only 12 cases of pituitary aspergillosis have been reported, all summarized in Table , along with our present case (No. 1).…”
Section: Reported Cases Of Pituitary Aspergillosismentioning
confidence: 63%
“…Pituitary aspergillosis is an extremely rare presentation for Aspergillus infection and is often misdiagnosed as a pituitary tumor . To our knowledge, only 12 cases of pituitary aspergillosis have been reported, all summarized in Table , along with our present case (No. 1).…”
Section: Reported Cases Of Pituitary Aspergillosismentioning
confidence: 63%
“…Visual deficits were prominent for twelve patients, while only six cases detailed abnormal pituitary function. [4][5][6][7][8][9] The visual deficits often present and progress quickly and rarely improve after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relation between fungal infection and tumor formation is not understood. Several studies have shown that aspergillus infection can cause aspergilloma formation at various sites [2][3][4][5][6][7] , and some studies have described bronchogenic carcinoma caused by pulmonary aspergilloma 6 , whilst others have described only the coexistence of aspergilloma and carcinoma in the same cavity 5,7 . Although it is not understood how aspergillosis could induce carcinoma formation, the chronic inflammation caused by prolonged fungal infection might be carcinogenic.…”
Section: ⅲ Discussionmentioning
confidence: 99%
“…The most frequent site of human aspergillus infection is the lung, followed by the liver, spleen, bone, meninges, and paranasal sinuses 2 . In several reports, the coexistence of fungal infection and malignancy has been noted in the brain and thoracic cavity [3][4][5][6] . Moreover, Tanaka et al 7 reported the coexistence of aspergillosis and squamous cell carcinoma (SCC) in the maxillary sinus.…”
Section: ⅰ Introductionmentioning
confidence: 99%